Birth trauma: characterization and thematic analysis of traumatic birth experiences revealed on social media - Julia Camilleri; Anita Nelson (Contraception and Reproductive Medicine)
Abstract Background Although guidelines exist for the diagnosis and treatment of those who have endured traumatic birth, the term itself is poorly defined and has no clear identifying criteria. Birth trauma has profound long-term health and quality of life sequelae. This study assessed how birth trauma was described by women who had experienced it and were followers of a public social media platform interested in the topic to help better characterize the term. Methods We posted an invitation on the Birth and Trauma Facebook Support Group website to English speaking people over age 18 years with personal experience with birth trauma to participate in an anonymous, beta-tested, IRB-approved, 18-question survey. The survey asked about demographic information, personal experiences with what the respondents perceived to be birth trauma, the settings in which it occurred and any longer-term impacts they may have noted. We calculated the percentage of participants' responses to objective questions and performed thematic analysis of the answers to the open-ended questions. Results From the approximately 6,000 online group followers, we received 1,362 responses (response rate = 22.7%). The average age of respondents was 25 years; 55% were multiparous, and half of those latter participants reported having suffered multiple episodes of traumatic birth. Most participants (73%) reported that trauma occurred during labor and delivery; 17% said it occurred at any time during pregnancy and 32.5% reported their trauma in the immediate postpartum period. Three major and two minor themes emerged to characterize their traumatic experiences. Physical trauma was the most common theme- pain, lacerations/incisions, surgical complications, hemorrhage, unplanned C-Sects. (41.4%), but emotional- fear/anxiety about death, complications, judgment, infection, and feelings of disempowerment (21%) and unexpected adverse outcomes- premature births, intensive care stays, complications due to pre-existing chronic illness/history of infertility (17.6%) were also prevalent. Conclusion Respondents generalized “birth trauma” to include experiences throughout pregnancy. Our results suggest that many women are entering pregnancy unprepared for experiences that can have significant long-term impacts. Even multiparous women reported unexpected outcomes that they found traumatic. The themes derived from this survey provide insight into how multifaceted and complex birth trauma is, and how challenging it may be to tailor individual trauma-informed care.